Effects of gallic acid on expressions of MMP-2 and MMP-9 through the pathway of p38/JNK in C6 glioma cells - GÜLSOY, NAGİHAN (My University, 2023)
In our study, the effects of gallic acid (GA), a natural therapeutic agent, on oxidative stress biomarkers and MMP-2 and MMP-9 expressions via the p38/JNK pathway in C6 glioma cells were investigated. The toxicity of GA was determined by the WST-1 method. JNK, p38 and MMP-2/-9 mRNA expressions in the cell line were detected by RT-qPCR. JNK/SAPK, Grap-2/p38 and MMP-2/-9 protein levels were analyzed by using ELISA methods. Biochemical markers were analyzed. GA reduced the cell viability of C6 glioma cells after 24, 48 and 72h of treatment. The expression levels of MMP-2 and MMP-9 mRNA decreased in C6 glioma cells treated with 150 mu g/ml GA for 24 and 48h compared to the control cells. Unlike SOD activity, GA treatment significantly increased PCO and MDA levels in the cells treated with 150 mu g/ml GA for 24 and 48h compared to the non-treated cells. According to our results, GA inhibited the proliferation of C6 glioma cells. Also, it reduced MMP-2 and MMP-9 expressions and increase oxidative stress. Therefore, GA may have preventive effects on gliomas progression and/or invasion.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Matrix metalloproteinase; oxidative damage; gallic acid; glioma; toxicity; CANCER-CELLS; JNK; PROLIFERATION; INVASION; PROTEIN; BREAST; ANGIOGENESIS; INHIBITOR; VIABILITY; SP600125; Matrix metalloproteinase; oxidative damage; gallic acid; glioma; toxicity